2016
DOI: 10.1021/acs.joc.6b02385
|View full text |Cite
|
Sign up to set email alerts
|

9,10-Dicyanoanthracene Catalyzed Decarboxylative Alkynylation of Carboxylic Acids under Visible-Light Irradiation

Abstract: A metal-free, visible-light-induced photocatalytic procedure for decarboxylative alkynylation of carboxylic acids was reported. With 9,10-dicyanoanthracene as the photoredox catalyst, the reaction covered a broad scope of α-amino acids, α-oxo acids, and α-keto acids with blue LED irradiation at room temperature under an atmosphere of argon, delivering alkynyl products in moderate to excellent yields. Natural sun light also promoted this alkynylation strategy. This work represents the first example of an organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…[6] Recently, a more cost-effective procedure has been developed using cheap and easily handled 9,10-dicyanoanthracene as the photocatalyst. [7] While the above mentioned strategy of photocatalytic decarboxylative alkynylation is quite remarkable, the homogeneous nature of the photocatalysts used in the process makes their separation from the product as well as their recycling difficult, which has significantly restricted the industrial application of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently, a more cost-effective procedure has been developed using cheap and easily handled 9,10-dicyanoanthracene as the photocatalyst. [7] While the above mentioned strategy of photocatalytic decarboxylative alkynylation is quite remarkable, the homogeneous nature of the photocatalysts used in the process makes their separation from the product as well as their recycling difficult, which has significantly restricted the industrial application of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in experimental realization of this proposal clearly lies in identifying reaction conditions that are conducive for simultaneously supporting operations of all of the above mentioned events. Green LEDs (3.0 W, l = 530 � 10 nm) were more effective than compact blue LEDs (3.0 W, l = 450 � 10 nm) and fluorescent lamps (CFLs), indicating the higher photocatalytic activity of eosin Y in the presence of highintensity green light (Table 1, entries [12][13][14]. In contrast, other cyclic iodine(III) reagents methoxybenziodoxole (BI-OMe) and acetoxybenziodoxole (BI-OAc) gave even better results, while the reactivity with BI-OAc was the best ( Table 1, entries 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…[10] In the same year, Xiao and Waser group independently developed the visible-light triggered decarboxylative alkynylation of carboxylic acids with benziodoxolone (BI)-alkynes (Scheme 1, B). [12] Wang & Li's group reported a visible-light photoredox decarboxylative alkynylation of α-keto acids using bromoacetylenes as the alkynyl precursors and NHPI (N-hydroxyphthalimide) as the catalyst to give ynones under the irradiation of sunlight or blue LED light (Scheme 1, D). [12] Wang & Li's group reported a visible-light photoredox decarboxylative alkynylation of α-keto acids using bromoacetylenes as the alkynyl precursors and NHPI (N-hydroxyphthalimide) as the catalyst to give ynones under the irradiation of sunlight or blue LED light (Scheme 1, D).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Cheng et al. reported the first metal‐free decarboxylative alkynylation with 9,10‐dicyanoanthracene (DCA) as the photocatalyst (Scheme b) . However, EBX reagents, which are expensive and often troublesome to synthesize, are still needed as coupling partners.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In 2016, Cheng et al reported the first metal-free decarboxylative alkynylation with 9,10-dicyanoanthracene( DCA) as the photocatalyst (Scheme 1b). [10] However,E BX reagents, which are expensive and often troublesome to synthesize, are still neededa sc oupling partners. Another approachf or decarboxylations can be achieved by activation of the carboxyg roup through esterification to N-(acyloxy)phthalimides and subsequent reduction of the moiety.D ifferent cross-couplingr eactions can be carried out in this way.…”
Section: Introductionmentioning
confidence: 99%